2016
DOI: 10.1007/s11207-016-0995-x
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Hydrogen and Its Emission Lines in the Solar Corona

Abstract: Since the Lα rocket observations of (Gabriel, Solar Phys. 21, 392, 1971), it has been realized that the hydrogen (H) lines could be observed in the corona and offer an interesting diagnostic for the temperature, density, and radial velocity of the coronal plasma. Moreover, various space missions have been proposed to measure the coronal magnetic and velocity fields through polarimetry in H lines. A necessary condition for such measurements is to benefit from a sufficient signal-to-noise ratio. The aim of this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…The mean k/h ratio takes a value of 1.41 in both the tornadoes and in the rest of the prominence. This is a similar value as has been found previously (Schmieder et al 2014;Liu et al 2015;Levens et al 2016a;Vial et al 2016). The displacement of the k 3 feature from its stationary position at line centre gives an indication of how the frontmost layers of the prominence are moving along the line-of-sight.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The mean k/h ratio takes a value of 1.41 in both the tornadoes and in the rest of the prominence. This is a similar value as has been found previously (Schmieder et al 2014;Liu et al 2015;Levens et al 2016a;Vial et al 2016). The displacement of the k 3 feature from its stationary position at line centre gives an indication of how the frontmost layers of the prominence are moving along the line-of-sight.…”
Section: Resultssupporting
confidence: 89%
“…Under normal chromospheric conditions, where the Mg ii ions are collisionally excited, we would expect a k/h ratio of 2 and the plasma to be opti-cally thin. Previous prominence observations have shown typical k/h ratios of around 1.5 (Schmieder et al 2014;Liu et al 2015;Vial et al 2016;Levens et al 2016a), and NLTE models of Mg ii have found similar expected values (Heinzel et al 2014). Values lower than 2, as have been observed, suggest the presence of scattering in the emitting region, i.e.…”
Section: Mg II I K /I H Ratiosupporting
confidence: 61%
See 1 more Smart Citation
“…In general, the Mg II k line profile in on-disk observations has a central reversal in the emission peak within an even broader absorption component, which are produced by a complex radiative transfer process (Leenaarts et al 2013a,b;Pereira et al 2013). In off-limb observations, as long as there is no spatial overlap of different features along the line of sight, the profile is simple with a single, Gaussian-shaped peak indicative of optically thin emission (e.g., Schmieder et al 2014;Liu et al 2015;Vial et al 2016). This is indeed the case for most parts of our observed prominence.…”
Section: Event 2: 2013 October 19mentioning
confidence: 51%
“…The coronal number density of ionized hydrogen can be inferred by measuring the electron density from the VL polarised emission detected with Metis. Under the hypothesis of ionisation equilibrium, the ratio between neutral and ionized hydrogen atoms depends on the electron temperature, for example, see Vial & Chane-Yook (2016). The T e radial profiles can be selected from the literature.…”
Section: Diagnostic Techniquesmentioning
confidence: 99%